2021
DOI: 10.1111/ced.15007
|View full text |Cite
|
Sign up to set email alerts
|

Linear IgA bullous dermatosis following Oxford AstraZeneca COVID‐19 vaccine

Abstract: A case of linear IgA bullous dermatosis developing 3 days after the second dose of Oxford AstraZeneca COVID‐19 vaccine in an adult patient, suggesting a possible causal association. It is worth keeping in mind that COVID‐19 vaccination could induce immune‐mediated bullous disease in susceptible people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 5 publications
2
14
0
Order By: Relevance
“…While no cases of LABD have been reported with COVID‐19 infection, there are two reports of LABD being triggered by the recombinant Oxford‐AstraZeneca and mRNA Pfizer‐BioNTech COVID‐19 vaccines. In both these cases, eosinophils were seen in the infiltrate, although not as dense as seen in our patient 16 , 17 In these reports, a 61‐year‐old male developed LABD 3 days after the second dose of the Oxford‐AstraZeneca COVID‐19 vaccine and was treated with oral prednisolone with improvement, 16 while a 71‐year‐old male developed LABD 3 days after the second dose of the Pfizer‐BioNTech COVID‐19 vaccine and was treated with topical corticosteroids with improvement. 17 …”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…While no cases of LABD have been reported with COVID‐19 infection, there are two reports of LABD being triggered by the recombinant Oxford‐AstraZeneca and mRNA Pfizer‐BioNTech COVID‐19 vaccines. In both these cases, eosinophils were seen in the infiltrate, although not as dense as seen in our patient 16 , 17 In these reports, a 61‐year‐old male developed LABD 3 days after the second dose of the Oxford‐AstraZeneca COVID‐19 vaccine and was treated with oral prednisolone with improvement, 16 while a 71‐year‐old male developed LABD 3 days after the second dose of the Pfizer‐BioNTech COVID‐19 vaccine and was treated with topical corticosteroids with improvement. 17 …”
Section: Discussionsupporting
confidence: 56%
“…While bullous pemphigoid (BP) has been the most commonly reported vaccine-related AIBD, linear IgA bullous dermatosis (LABD) has also been reported in the setting of both the recombinant Oxford-AstraZeneca and messenger RNA (mRNA) Pfizer-BioNTech COVID-19 vaccines. 16,17 Here, we present a case of LABD triggered by the mRNA Moderna COVID-19 vaccine booster with histopathological features resembling BP that required confirmation with direct immunofluorescence (DIF) and indirect immunofluorescence (IIF) studies for accurate diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 195 articles was retrieved and after the screening, 20 articles were finally included for the review. A total of 35 AIBDs cases (including our case) were found, as shown in Table 1 [7] , [8] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] . The sub-epithelial diseases were the most frequent, accounting for 28 cases (80.0%), specifically 26 cases of BP (74.3%) and 2 case of LABD (5.7%).…”
Section: Resultsmentioning
confidence: 99%
“…Of note, the patient received the Oxford AstraZeneca vector vaccine, which is not an mRNA vaccine. 6 Various mechanisms exist that could potentially explain our patient's heightened immunogenicity following her COVID-19 vaccination. One possible mechanism lies within the role of certain vaccine adjuvants.…”
Section: Discussionmentioning
confidence: 99%
“…To date, there have been only 2 other reported cases of LABD potentially associated with COVID-19 vaccination. 5,6 Coto-Segura et al 5 reported on a 71year-old man, who developed small vesiculobullae, some in a rosette-like pattern, over the thighs 3 days after receiving a second booster of the Pfizer COVID-19 vaccine. The patient was not taking any concomitant drugs at the time of his Pfizer COVID-19 vaccine booster.…”
Section: Discussionmentioning
confidence: 99%